Existence and Uniqueness of the Solution for an Inverse Problem of a Fractional Diffusion Equation with Integral Condition. (6th April 2022) - Oussaeif, Taki-Eddine; Antara, Benaoua; Ouannas, Adel; Batiha, Iqbal M.; Saad, Khaled M.; Jahanshahi, Hadi; Aljuaid, Awad M.; Aly, Ayman A.
Abstract : The solvability of the fractional partial differential equation with integral overdetermination condition for an inverse problem is investigated in this paper. We analyze the direct problem solution by using the "energy inequality" method. Using the fixed point technique, the existence and uniqueness of the solution of the inverse problem on the data are established.